The Ethnic Structure of the Population of the Bukhara Emirate - Rakhmatov Khayrulla Bozorboevich (Researchparks Publishing, 2021)
The article summarizes the researcher's views on the ethnic composition of the Bukhara Emirate population in the second half of XIX century - beginning of the XX century. It mainly concerns the administrative-territorial structure of the Bukhara Emirate, its population, population structure, the territory of ethnic groups and the language spoken. The author also draws attention to the fact that the Zarafshan Valley played a particularly important role in studying the ethnic composition of the Bukhara Emirate's population in the early twentieth century and the problem of ethnotoponyms